THE FORGE OF POLISH PHILOLOGISTS AT VASYL STEFANYK PREKARPATHIAN NATIONAL UNIVERSITY: HISTORY AND PROSPECTS - Lesiuk, Mykola (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Abstract. Mykola Lesyuk's article "Forge of Polish Philologists in Ivano-Frankivsk" made a brief overview of the history of the discovery, formation and development of polonistics at the Vasyl Stefanyk Precarpathian National University. In fact, in 2023 it is 30 years from the time of opening of the speciality "Polish language and literature", and therefore the department of the Slavic languages of this university. The article describes the numerous names of people who contributed to the discovery of a new speciality, helped to strengthen the material base of the department, and put on the professional basis of teaching the Polish language. The purpose of the article. The article aims to show what difficulties the management of the department and the faculty had to overcome in the first years of formation of the speciality "Polish language and literature", stages of its development, cooperation with Polish scientific institutions and scientists, creation and constant strengthening of the material base, formation of phono-, audio- and video library, work with invited teachers from Poland and more. Methods of accumulation of facts. The main method used in writing the article is the analysis of the twists and turns, which had to be overcome in the organization of the educational process in the speciality "Polish language and literature", review of the letters to officials and individuals, analysis of the contingent of this speciality, the number of prepared Polish philologists, in particular those who continued to do scientific research, defended scientific thesis and more.